PROFIL KARAKTERISTIK DAN ANTIBIOTIK PASIEN ULKUS KAKI DIABETIK DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE PONTIANAK - Robiyanto, Robiyanto (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2016)
The increasing numbers of diabetic foot ulcus (DFU) patients every year causes its antibiotic profile therapy need to be studied. This observational study was aimed to profiling the patient characteristic and antibiotic therapy in DFU patients. The design of study was cross-sectional and data were presented descriptively. Data sampling was taken retrospectively. Samples in this study were DFU patients, aged between 18 to 65 y.o., which received antibiotic therapy at RSUD Sultan Syarif Mohamad Alkadrie in 2015. Result showed that the number of DFU patients between women and men was almost equal (53,13% vs 46,87%). 90,63% of DFU patients were above 45 y.o. The percentage of DFU patients that treated at RSUD Sultan Syarif Mohamad Alkadrie was 5.77% from total diabetic mellitus patients. All of the DFU patients in this study were diabetic mellitus type 2 patients (100%). Type of antibiotic that was mostly prescribed was fluoquionolone group (levofloxacin)(27.69%). 75% DFU patients in this study received the combination therapy of antibiotic.